Philippine technocracy and the politics of economic decision making during the Martial Law period - Tadem, Teresa S. Encarnacion (2013)
This paper seeks to elucidate the Philippine technocracy’s rise into the power elite as well as its fall from position during the martial law period (1972- 1986). It aims to bring in the insights of the technocrats concerning their role in President Ferdinand E. Marcos’s authoritarian regime and their views of the nature of the politics, which facilitated as well as impeded the economic decision-making process. The paper argues that the technocracy’s technical expertise and shared development vision with the leadership and the country’s major donors, the International Monetary Fund (IMF) and the World Bank, provided their power base.This was, however, continually challenged by the other economic power blocs which consisted mainly of factions within the technocracy, the Marcos cronies, and that of the First Lady Mrs. Imelda Marcos. For as long as the technocracy could access the needed IMF/World Bank loans for the country, the leadership gave it substantive bargaining leverage. This, however, would deteriorate with the country’s economic and political instability as brought about by failed technocratic policies and worldwide economic recession in 1981 and the burgeoning antidictatorship movement spawned further by the 1983 assassination of ex-Senator Benigno Aquino Jr. The technocracy’s loss of power was further aggravated by Marcos’s failing health giving more clout to Mrs. Marcos’s power bloc. What contributed to the technocracy’s ultimate demise was their alienation from the general public as brought about by their vast differing perceptions of the causes of corruption, underdevelopment, and human rights abuses of the regime.
Keywords: Technocracy; Martial law; Decision making -- Political aspects; Marcos administration